(untitled) (Research, Society and Development, 2020)
Homeopathy is a therapeutic system that contemplates the entire human being at the expense of isolated diseases, and can even be used in cases of viral diseases. The means of contagion of viruses can occur in several ways, which can spread quickly between beings and replication in the individual occurs quickly, and can affect several organs. The drugs currently used to fight viruses, produce many adverse effects such as liver dysfunction and hematological changes. Based on the circumstances of viral conditions, the study aimed to search the literature for studies that report the use of homeopathic therapy in antiviral treatment. The research was carried out through bibliographic analysis using the literature review method in the Scientific Electronic Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Information System (LILACS) databases in articles published between the period of 2015 to 2020, in Portuguese and English, which meet the inclusion and exclusion criteria, with 7 articles selected. Thus, the present study reported by the authors, shows through research and tests carried out, that the use of homeopathy is a treatment that can lead to the improvement of individuals in viral conditions, in addition to becoming a cheaper method, and with reduction or absence of adverse effects in relation to the allopathic method in the most used antiretroviral treatment today.